What Does Zionism Mean to Canadian Jews? A Longitudinal Study of Semantic Drift - Brym, Robert (Canadian Jewish Studies / Études juives canadiennes, 2025)
A late summer 2024 web panel survey of 588 Canadian Jews found that 49 percent of respondents do not identify as Zionists. Anti-Zionists rejoiced that rejection of Zionism is widespread in the Jewish community. Zionists took comfort from the same survey’s finding that 94 percent of Canadian Jews said they support the existence of a Jewish state in Israel. Many observers were puzzled over how both findings could be accurate at the same time. This paper begins to address that issue. It is based mainly on a January 2025 follow-up survey of 332 of the original respondents. The follow-up finds evidence that refusal to label oneself a Zionist is largely due to the increasingly negative connotation of the word Zionism—what linguists call “semantic drift.” This paper also finds that just 1 percent of Canadian Jews (4 percent of those who reject the Zionist label) say they are anti-Zionists.